547 Supernormal conduction of an accessory pathway: the case of a young sportsman. (8th December 2021) - Robles, Antonio Gianluca; Petrungaro, Mattia; Penco, Maria; Romano, Silvio; Sciarra, Luigi
Abstract: Aims: Ventricular pre-excitation is defined by the presence of all of the following electrocardiographic criteria: PQ interval duration ≤120 ms, QRS duration ≥120 ms, and presence of δ wave (defined as initial 'slurring' of the QRS complex). Ventricular pre-excitation together with the presence of symptoms (orthodromic and/or antidromic atrioventricular reentry tachycardia, atrial fibrillation) defines Wolff–Parkinson–White (WPW) syndrome. The anatomical substrate of ventricular pre-excitation consists of an extranodal accessory atrio-ventricular connection: the so-called Kent bundle. Such pathways can have antegrade, retrograde, or mixed conductive properties. Accessory pathways endowed with anterograde conductive capability may be responsible for manifest, intermittent, or non-manifest ventricular pre-excitation depending on whether it is respectively always visible on the ECG, not always visible on the ECG and not visible on the ECG even though the pathway has the ability to antegrade conduction. The rare phenomenon of supernormal conduction of anomalous pathways is part of the manifest pre-excitation, which represents the topic of the case reported below. Methods and results: We report the clinical case of a young not agonist sportsman undergoing an electrophysiological study (SEF) because of he is suffering from ventricular pre-excitation. The SEF did not showed the inducibility of arrhythmias and, at the same time, apparently it showed low risk characteristics of the pathway even during adrenergic stimulus. However, a careful study, performed with atrial stimulation with couplings up to refractoriness of the atrioventricular node revealed supernormal conduction properties of the Kent bundle which proved to have high risk characteristics according to current guidelines and, therefore, was effectively treated with catheter ablation. Conclusions: This case invites us to careful studying of accessory pathways properties, especially since, although rare, they may possess supernormal conduction characteristics capable of determining high ventricular rates in the case of sustained atrial tachyarrhythmias, especially in conditions of adrenergic hyperactivity.